(untitled) (Circe de clásicos y modernos, 2018)
According to humanist appreciation the heroic and didactic poetry ranks highest in the hierarchy of poetical genres. Among the numerous productions, IJSEWIJN- SACRÉ (1998) distinguish the burlesque epic poems. In book IV of Rusticatio Mexicana, Rafael Landívar introduces burlesque passage when inserts the battles of the cochineals or purple worms. KERSON (1990) thinks that the mock –heroic style is destined to arouse the reader. But the burlesque treatment of the battles has an exemplar purpose.